Compostos antioxidantes e quantificação do eugenol de extratos das folhas de cravo da índia (Syzygium aromaticum) obtidos por diferentes métodos de extração - Frohlich, Paula Cassiana (2023)
Clove (Syzygium aromaticum) is an aromatic tree of the family Myrtaceae of great industrial interest due to its eugenol (phenylpropanoid) composition, employed in the pharmaceutical, cosmetics, food, and agriculture areas. The method most used by industries to obtain oil from dried flower buds and clove leaves is steam distillation. However, this extraction method has some disadvantages, such as long extraction time and high temperatures in the process, which may cause degrade some of the active compounds. Thus, searching for alternatives to extract cloves with high yields, shortened extraction times, and a good quality extract is important. In this context, the present study aimed to evaluate extracts from clove leaves regarding yield, chemical composition, phenolic compounds, and antioxidant activity, obtained by several extraction methods: Soxhlet, ultrasound-assisted, supercritical carbon dioxide under high pressures, and pressurized-liquid extraction. Soxhlet extractions (8 hours) were performed with the solvents n-hexane, ethyl acetate, and ethanol. The extracts obtained with ethanol presented the best results concerning extraction yield (26.25%). Clove leaves were then subjected to ultrasound-assisted extraction (UAE) with the solvent ethanol, following a central composite experimental design to evaluate the effects of time (5 min – 25 min), amplitude (25% - 85%), solvent/sample ratio (15 mL g-1 - 35 mL g-1), and temperature (30 ºC – 70 °C) in the extract yield, eugenol yield, and their antioxidant activity. The results were compared to the ones obtained with the conventional method of maceration (ME). The optimum condition for extract yield was reached with an extraction time of 25 min, an amplitude of 85%, a solvent/sample ratio of 35 mL g-1, and a temperature of 70 ºC, and the result (14.63%) was three times higher than conventional extraction. The analysis of the extracts obtained for both methods revealed the presence of eugenol in the composition, with the highest yield of 2.71 g eugenol per kg leaves using the UAE method (20 min, 70%, 20 mL g-1, 40 ºC), while the ME method provided 1.30 g eugenol per kg leaves. In the pressurized-liquid extractions (40, 50, and 60 °C; 100 bar and 20 min), ethanol was the solvent. In this extraction process, at 60 °C the highest extract yield (6.54 %) was obtained, and an eugenol yield of 2.66 g eugenol per kg leaves. The supercritical CO2 extractions (SFE) were performed in temperatures 40, 50, and 60 °C and pressures 200, 250, and 300 bar, with a volumetric flow rate of 3 mL min-1, and a total extraction time of 80 min. The highest yield obtained was 1.94 % at 60 °C and 220 bar. In this condition, the eugenol yield was 8.06 ± 0.025 g eugenol per kg leaves, the content phenolic compounds was 316.74 ± 0.29 µg GAE mg-1 and the antioxidant capacity was 3.02 ± 0, 05 µmol Trolox mg-1 and 17.79 ± 0.24 µmol Fe2+mg-1, results that were considered optimal among the non-conventional methods evaluated. The extracts obtained by SFE showed the best extract yields, however, higher concentration of the compound of interest, eugenol, in addition to high antioxidant capacity and content of phenolic compounds. The other methods (UAE and PLE) evaluated, despite having a lower concentration of eugenol, showed a higher yield of extracts, as well as satisfactory antioxidant capacity and content of phenolic compounds.